The work-family balance in light of globalization and technology - Heras, Mireia las; Chinchilla, Nuria; Grau, Marc (Cambridge Scholars Publishing, 2017)
Technology is changing the way we integrate work and family life today. In an age in which information technology has brought the promise of autonomy and control by allowing asynchronous communications; in which work systems have enabled people to work from various times and in various locations; and in which work and non-work boundaries have as a result been blurred, the work and family interface needs to be reconsidered. This collection is the result of a careful selection of articles presented at the Sixth International Conference for Work and Family organized by the International Center fo.